"Through the looking glass: envisioning new library technologies" changing the legal foundation of the internet: Section 230. Issue 2 (17th February 2022) - Fernandez, Peter
Abstract : Purpose: This paper aims to examine how changes to the regulatory framework of Section 230 may impact the development of internet-powered websites and technologies. Design/methodology/approach: Specific legislative proposals serve as a jumping off point to clarifying underling principles that impact how the internet operates and is impacted by legal frameworks. Findings: Issues of power and the law interact with the technology that undergirds the internet in complicated ways. Once established, many of these dynamics can become invisible to the average user. Originality/value: New regulations for the internet are constantly being proposed. Many of them would directly impact libraries. Librarians need to understand these underlying dynamics to successfully navigate the changes that are to come (or help avoid them).